Citizens who inject drugs: the 'Fitpack' study - Lenton, Simon; Kerry, K.; Tan-Quigley, A.; Greig, R. (2000)
Most injecting drug users have never been in drug treatment yet much research is done on samples with high treatment rates drawn from agency and peer recruited populations. This study accessed drug injectors with little or no prior drug treatment, described their characteristics, BBVI risk behaviours and feedback on services. Its results challenge some stereotypes about citizens who inject drugs. A sample of 511 'hidden' drug injectors, of whom only 28.7% had any specialist drug treatment agency contact, completed a questionnaire which was distributed with 'Fitpack' needle packs sold through community pharmacies in WA. The mean age of respondents was 26.2 years, 43.4% were women, 44.3% were living with their sexual partner, 41.7% were parents, and 46.4% were employed, mostly in full time work. In the previous month 61.2% had injected less frequently than daily. The study accessed a diverse group of drug injectors not typically seen in agency and peer recruited research. They provided useful feedback about how harm reduction strategies among injectors can be improved. However, they also reported higher rates of injecting and sharing than previously found in traditionally recruited samples of injectors which suggests there is no room for complacency regarding the potential for BBVI transmission in this group